Pilot clinical study of ascorbic acid treatment in cardiac catheterization. (28th June 2019) - Sun, Lue; Igarashi, Tomonori; Tetsuka, Ryoya; Li, Yun-Shan; Kawasaki, Yuya; Kawai, Kazuaki; Hirakawa, Haruhisa; Tsuboi, Koji; Nakamura, Asako J; Moritake, Takashi
Abstract: Clinical radiodiagnosis and radiotherapy sometimes induce tissue damage and/or increase the risk of cancer in patients. However, in radiodiagnosis, a reduction in the exposure dose causes a blockier image that is not acceptable for diagnosis. Approximately 70% of DNA damage is induced via reactive oxygen species and/or radicals created during X-ray irradiation. Therefore, treatment with anti-oxidants and/or radical scavengers is considered to be effective in achieving a good balance between image quality and damage. However, few studies have examined the effect of using radical scavengers to reduce radiation damage in the clinical setting. In this study, we administrated 20 mg/kg ascorbic acid (AA) to patients before cardiac catheterization (CC) for diagnostic purposes. We analyzed changes in the number of phosphorylated H2AX (γH2AX) foci (a marker of DNA double-strand breaks) in lymphocytes, red blood cell glutathione levels, blood cell counts, and biochemical parameters. Unfortunately, we did not find satisfactory evidence to show that AA treatment reduces γH2AX foci formation immediately after CC. AA treatment did, however, cause a higher reduced/oxidized glutathione ratio than in the control arm immediately after CC. This is a preliminary study, but this result suggests that reducing radiation damage in clinical practice can be achieved using a biological approach.